Analisis Bentuk-bentuk Cyberbullying yang Terjadi Pada Selebgram dalam Media Sosial Instagram: (Studi Kasus Selebgram Bowo Alpenliebe) - Larasati Nadira Putri; Yani Osmawati (Universitas Budi Luhur, 2019)
Social media is a platform for disseminating information in a very significant ways, social media can engage the community into a new cultural pattern. Ease in playing the internet and social media made a lot of people use it, however, all this convenience is not always positive, many forms of crime that occur through social media are the result of people who abuse this technology advances, one of them is cyberbullying. Cyberbullying can be described as an intentional act by sending an electronic texts that contain mocking, disapproval or harassment through social media applications. Social media applications are believed to be one of the main causes of the rise of cyberbullying. This is caused by the ease of downloading an application, by only having an adequate internet network and gadget or smartphone. Instagram becomes one of the most widely used social media platforms, especially in Indonesia. Instagram's existence is also supported by Selebgram. Selebgram is a status that given to someone who is famous on social media, in this case Instagram, selebgram’s popularity can not be seperated from how they present themselves through their Instagram account. However, behind all the fame and benefits they can be obtained as a selebgram, they must be mentally strong to face a variety of all kind of negative comments from other Instagram users that can be categorized as act of cyberbullying.